The Effect of Compensation and Leadership Style on Turnover Intention with Work Motivation as Intervening Variable at PNM Mekaar Regional Mojokerto - Danang Setya Budi; Adi Susilo Jahja (Formosa Journal of Sustainable Research, 2023)
This research investigates the factors affecting turnover intention at PNM Mekaar Regional Mojokerto. Methods of data collection using questionnaires and interviews. We collect data from a sample of 243 respondents. Using the AMOS application, we perform statistical tests using Structural Equation Modeling (SEM). The results reveal that compensation and leadership style positively and significantly influence work motivation; however, they demonstrate a negative and significant influence on turnover intention. Additionally, work motivation does not considerably affect turnover intention. Furthermore, the mediating role of work motivation in the relationship between compensation, leadership style, and turnover intention is nonexistent